Phylogenetic relationships of the Asian palm civets (Hemigalinae & Paradoxurinae, Viverridae, Carnivora) - Patou, Marie-Lilith; Debruyne, Régis; Jennings, Andrew P.; Zubaid, Akbar; Rovie-Ryan, Jeffrine Japning; Veron, Géraldine (Elsevier Inc., 2008)
The Viverridae (Mammalia, Carnivora), one of the least studied groups of carnivorans, include two subfamilies of Asian palm civets: Hemigalinae and Paradoxurinae. The relationships between and within these two subfamilies have never been thoroughly tested using an extensive molecular sample set. In this study, we gathered sequences of four genes (two mitochondrial: Cytochrome b and ND2 and two nuclear: β-fibrinogen intron 7 and IRBP exon 1) for eight of the eleven extant species representing these two subfamilies. The results showed that: (1) the Asian palm civets (Hemigalinae and Paradoxurinae) have a single origin and form the sister-group of the (Genettinae + Viverrinae) clade, (2) the Hemigalinae (including the otter civet Cynogale bennettii) are monophyletic, (3) the Paradoxurinae are monophyletic and (4) the small-toothed palm civet (Arctogalidia trivirgata) is an early offshoot within the Paradoxurinae. Using a relaxed molecular clock analysis, the differentiation of the (Hemigalinae + Paradoxurinae) was inferred to occur in the Late Oligocene/Early Miocene.